Freefall eaudiobook - Heitzmann, Kristen (Recorded Books Inc., 2013)
Freefall, a CBA best-seller by Christy Award winner Kristen Heitzmann, swirls with gripping suspense, heartstopping action, and blossoming romance. When an injured stranger staggers down a Hawaiian mountainside and into her backyard, Monica believes God has directed this mysterious young lady to her. But Monica's brother, an insurance fraud investigator, isn't so sure. He finds it hard to believe this green-eyed outsider doesn't know who she is, what has happened, or where she is.